A case of idiopathic First Bite Syndrome responding to carbamazepine. (27th February 2019) - Wemyss, C.; Gibson, J.; Ryan, K.
Abstract: First Bite Syndrome (FBS) is a painful condition which classically presents as severe pain in the pre‐auricular region, initiated on the first bite of a meal. It is usually associated with a history of upper neck surgery or tumour of the parotid salivary gland or parapharyngeal space (PPS). Some propose that FBS arises from damage to, or resection of, the cervical sympathetic trunk resulting in loss of sympathetic innervation to the parotid salivary gland. Idiopathic FBS has been reported only a handful of times in the literature. We present the case of a 51‐year‐old male, urgently referred to the Department of Oral Medicine, with a 3‐week history of severe, sharp, unilateral pain from the right angle of mandible, intensity described as '20/10', occurring only on the first bite of eating. This would diminish over 2 min. Clinical examination revealed tenderness over the right condylar neck and angle of mandible only. FBS was suspected and the patient immediately started on carbamazepine. An urgent MRI displayed no abnormalities of the temporomandibular joints, PPS, trigeminal nerve or parotid gland. Restorative Dentistry review confirmed no odontogenic or occlusal cause and on review, 4 months later the patient reported complete resolution of symptoms on 200 mg of carbamazepine three times daily. This case highlights the importance of taking a thorough pain history. Patients with symptoms of FBS and no history of surgery to the neck should have an MRI to rule out parotid gland or PPS tumour. Carbamazepine can be successful in treating idiopathic FBS and can resolve symptoms completely.